Effective therapeutic communication by nurses improves inpatient satisfaction on Hospital Wards - izzah, Nur; Khasanah, Elsya Alfirotul; Kusuma, Nur Intan (International Journal of Health Science and Technology, 2025)
In an era of global competition and increasing societal demands, the quality of healthcare services and patient satisfaction are important indicators of hospital quality. Nurses are the healthcare workers with the highest frequency of interaction with patients in inpatient wards, and communication is crucial. Effective and high-quality communication is key to nurses' success in carrying out their roles and functions to improve patient satisfaction. This study aims to examine the relationship between nurses’ therapeutic communication and patient satisfaction in the inpatient ward. This study employs a descriptive correlational design with a cross-sectional approach. The sample used was 67 inpatients who were selected proportionally based on the number of patients in each treatment room using a proportional random sampling technique. A questionnaire was used as the measurement tool to measure therapeutic communication and patient satisfaction. Data analysis was conducted using Fisher’s Exact Test.The study indicated a significant relationship between nurses' therapeutic communication and patient satisfaction in the inpatient ward. Therefore, hospitals are strongly recommended to provide regular training and incorporate this skill into nurse performance evaluations to systematically improve the overall quality of care and institutional reputation.